2019
DOI: 10.1186/s40497-019-0189-8
|View full text |Cite
|
Sign up to set email alerts
|

The comparative analysis of marketing activities among rural women entrepreneurs in Fars province, Iran

Abstract: Entrepreneurship has become the crucial subject of discussion among social and economic development specialists as the key to solving problems and reducing obstacles to human development. On the other hand, marketing is also considered as a main factor for entrepreneurial businesses' survival and progress. Thus, low marketing skills in small businesses often lead to lower performance levels and higher risk failures. The present study aimed to identify and analyze the marketing activities among rural women entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Rashid et al (2020) found that women are more market-oriented than men which influences their business success. Whereby women are considered to emphasize more on developing relationship with customers than men (Rezaei-Moghaddam et al, 2019). In contrary, Ayub et al 2013argue that men are more market-oriented than women based on their ability to create innovative business ideas.…”
Section: Gender and Entrepreneurial Orientationmentioning
confidence: 99%
“…Rashid et al (2020) found that women are more market-oriented than men which influences their business success. Whereby women are considered to emphasize more on developing relationship with customers than men (Rezaei-Moghaddam et al, 2019). In contrary, Ayub et al 2013argue that men are more market-oriented than women based on their ability to create innovative business ideas.…”
Section: Gender and Entrepreneurial Orientationmentioning
confidence: 99%